ẢNH HƯỞNG CỦA NGUỒN CACBON, NITƠ VÀ NaCl ĐỐI VỚI SINH TRƯỞNG VÀ SINH TỔNG HỢP BACTERIOCIN CỦA CÁC CHỦNG LACTOCOCCUS PĐ14, PĐ2.9 VÀ BV20 - Đà, Nguyễn Thị; Tú, Hoa Thị Minh; Bình, Lê Thanh (Vietnam Journal of Science and Technology, 2012)
SUMMARY THE EFFECT OF CARBON, NITROGEN SOURCES AND NaCl ON THE GROWTH  AND BIOSYNTHESIS BACTERIOCINS OF LACTOCOCCUS  STRAINS PD14, PD2.9 AND BV20 Bacteriocin production has been affected by a number of factors including media composition, such as carbon, nitrogen sources, NaCl and fermentation conditions. Bacteriocins synthesized by Lactococcus strains PD14, BV20, PD2.9 inhibit the growth of some lactic acid bacteria and especially Staphylococcus aureus, Bacillus subtilis. Optimal production of bacteriocin PD14 (795 AU/ml) was recorded in MRS broth with an initial sucrose of 25 g/l, 0.1% (NH4)2HPO4 as sole nitrogen source. Bacteriocin PD2.9 was produced in MRS broth with 15 g/l sucrose and was supplemented with (NH4)2HPO4, NH4H2PO4. Bacteriocin BV20 produced in MRS broth when glucose was replaced with 20 g/l sucrose. Bacteriocin BV20 production, on the other hand, was more influenced by nitrogen content, but increased to 795 AU/ml when glucose was replaced with sucrose, or when MRS broth was supplemented four salts as NH4NO3,(NH4)2HPO4, NH4H2PO4, NH4Cl. Keywords. Bacteriocin PD14, PD2.9, BV20, carbon, nitrogen source.